Ultrasound: an indispensable tool to evaluate the outcome of surgical approaches in patients affected by hidradenitis suppurativa. (6th May 2020) - Marasca, C.; Marasca, D.; Megna, M.; Annunziata, M.C.; Fabbrocini, G.
Abstract : Linked article: L. Fertitta et al. J Eur Acad Dermatol Venereol 2020;34: e412–e413. https://doi.org/10.1111/jdv.16359 .